2021
DOI: 10.3389/fmicb.2021.724449
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Delivery Mode on the Gut Microbiota and Health: State of Art

Abstract: The delivery mode is an important factor driving alteration in the gut microbiota during the neonatal period. Several studies prove that the alteration of gut microbiota induced by cesarean section could influence the activation of intestinal epithelial cells and the development of immune system. Further, some autoimmune and metabolic disorders may be related to the microbiota dysbiosis in infants caused by cesarean section. It is noteworthy that probiotics could promote the intestinal microecology, which may … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 81 publications
0
26
0
1
Order By: Relevance
“…Some limitations to microbiome data interpretation should be acknowledged, including its cross-sectional/pilot design, which does not allow to adjust for mode of delivery and breastfeeding, factors known to shape the composition of the microbiota [19,43–48]. Likewise, the lack of a HUU control group limits the possibility to weigh the effects of intrauterine viral exposure vs. vertical HIV infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some limitations to microbiome data interpretation should be acknowledged, including its cross-sectional/pilot design, which does not allow to adjust for mode of delivery and breastfeeding, factors known to shape the composition of the microbiota [19,43–48]. Likewise, the lack of a HUU control group limits the possibility to weigh the effects of intrauterine viral exposure vs. vertical HIV infection.…”
Section: Discussionmentioning
confidence: 99%
“…However, they cannot rule out that the observed modifications of the gut microbiota in HEI may have a role in fueling persistent peripheral immune activation and inflammation [10]. Some limitations to microbiome data interpretation should be acknowledged, including its cross-sectional/ pilot design, which does not allow to adjust for mode of delivery and breastfeeding, factors known to shape the composition of the microbiota [19,[43][44][45][46][47][48]. Likewise, the lack of a HUU control group limits the possibility to weigh the effects of intrauterine viral exposure vs. vertical HIV infection.…”
Section: Discussionmentioning
confidence: 99%
“…We also found the prevalence of overweight and obesity in students delivered by cesarean section were higher. A recent study has shown cesarean section could affect the colonization pattern of intestinal bacteria in infants, which might lead to overweight and obesity in children and adolescents [ 23 ]. First born was one risk factor for overweight and obesity in our study, although the reasons weren't clear.…”
Section: Discussionmentioning
confidence: 99%
“… 5 , 30 Similarly, a thorough understanding of how cow’s milk formula and cesarean section births result in dysbiosis and increase susceptibility to allergy and asthma development can serve as a scientific rationale for advocating for breast feeding and natural births to reduce the risk of the development of allergic diseases later in life. 31 , 32 Collectively, these examples demonstrate the important need to further develop continuing medical education curricula to include the most updated information about the role of the microbiome in disease pathogenesis as well as potential therapeutic applications to prevent the development and/or mitigate symptoms of diseases of public health importance in Saudi Arabia, such as allergies and asthma.…”
Section: Discussionmentioning
confidence: 99%